Heavy work and disability pension – a long term follow-up of Swedish construction workers - Järvholm, Bengt; Stattin, Mikael; Robroek, Suzan JW; Janlert, Urban; Karlsson, Berndt; Burdorf, Alex (Scandinavian Journal of Work, Environment & Health, 2014)
' ' OBJECTIVES ': 'The objective of this study was to investigate the occurrence of disability pensions over time among workers with physically demanding jobs. ' ' METHODS ': 'The occurrence of disability pension was prospectively studied between 1980–2008 among 325 549 Swedish construction workers. The risks for disability pension and years lost of working life were compared among 22 occupational groups, adjusting for age, body mass index, height, and smoking habits. ' ' RESULTS ': 'The risk varied considerably among blue-collar workers. For example, rock workers had double the risk of disability pension [relative risk (RR) 2.16, 95% confidence interval (95% CI) 1.96–2.39] compared to electricians. Most working years lost due to disability pensions (about 75%) were found among men >50 years, mainly due to musculoskeletal and cardiovascular diseases. The years of working life lost due to disability pension varied from 0.7 (salaried employees) to 3.2 years (rock workers) among occupational groups. ' ' CONCLUSION ': 'Work environment is an important predictor for disability pension among construction workers with those in physically heavy jobs having the highest burden of disability. If the purpose is to increase labor force participation for workers with heavy jobs, strategies to reduce physical demands at work among elderly workers are important.
Keywords: attributable risk; construction; construction worker; disability pension; employability; epidemiology; heavy work; insurance medicine; public health; Sweden